A unique case with positive anti‐myelin oligodendrocyte glycoprotein antibody presenting multiple brain lesions. Issue 2 (21st January 2020) - Matsumoto, Namiko; Sato, Kota; Hishikawa, Nozomi; Kawahara, Yuko; Takemoto, Mami; Ohta, Yasuyuki; Yamashita, Toru; Fujii, Kentaro; Kurozumi, Kazuhiko; Date, Isao; Takahashi, Toshiyuki; Abe, Koji
Abstract: The accurate diagnosis of anti‐myelin oligodendrocyte glycoprotein (MOG) antibody‐associated diseases is sometimes challenging due to its various central nervous system (CNS) lesions. Here, we report a 22‐year‐old man with positive anti‐MOG antibody presenting multiple brain lesions including a brainstem tumefactive demyelinating lesion (TDL), cortical edematous lesions, and a periventricular white matter lesion. These variety of lesions made the diagnosis challenging, especially because TDL is quite rare among MOG antibody‐associated disease patients. The present case suggests the importance to check anti‐MOG antibody for patients presenting atypical multiple CNS lesions.